Landscapes John Berger on art - Berger, John (Verso, 2016)
"With Portraits, world-renowned art writer John Berger took us on a captivating journey through centuries of art, situating each artist in the proper political and historical contexts. In Landscapes, a narrative of Berger's own journey emerges. Through his penetrating engagement with the writers and artists who shaped his own thought, Walter Benjamin, Rosa Luxembourg and Bertolt Brecht among them, Landscapes allows us to understand how Berger came to his own way of seeing. As always, Berger pushes at the limits of art writing, demonstrating beautifully how his painter's eyes lead him to refer to himself only as a storyteller. A landscape is, to John Berger, like a portrait, an animating, liberating metaphor rather than a rigid definition. It's a term, too, that reminds us that there is more here than simply the backdrop or 'by-work' of a portrait. Landscapes offers a tour of the history of art, but not as you know it"-- Provided by publisher.